2012
DOI: 10.4046/trd.2012.72.5.433
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Body Composition on Pulmonary Function

Abstract: BackgroundThe pulmonary function test is the most basic test method to diagnosis lung disease. The purpose of this study was to research the correlation of the body mass index (BMI), the fat percentage of the body mass (fat%), the muscle mass, the fat-free mass (FFM) and the fat-free mass index (FFMI), waist-hip ratio (WHR), on the forced expiratory volume curve.MethodsBetween March and April 2009, a total of 291 subjects were enrolled. There were 152 men and 139 female (mean age, 46.3±9.92 years), and they we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 13 publications
2
32
2
Order By: Relevance
“…Restrictive type of lung function abnormalities are frequently observed among obese subjects responsible for alteration in respiratory mechanics [60]. Abdominal and thoracic fat deposition are associated with work of breathing [60,61]. Our results indicate a significant decline in the predicted values of both FEV 1 and PEFR with increasing body fat%.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Restrictive type of lung function abnormalities are frequently observed among obese subjects responsible for alteration in respiratory mechanics [60]. Abdominal and thoracic fat deposition are associated with work of breathing [60,61]. Our results indicate a significant decline in the predicted values of both FEV 1 and PEFR with increasing body fat%.…”
Section: Discussionsupporting
confidence: 59%
“…Several studies reported no significant differences in FEV 1 , FVC, FEV 1 /FVC ratio and FEF between obese and non-obese subjects [1,57,58]. Obesity is the combination of fatty mass and body masculinity, whereas BMI can interpret only body structure [57,59,60].The effects of body fat% on the pulmonary function values have also been examined in the present study, a topic which hasn't received much attention. Our study showed body fat% to be a better indicator of the lung function alterations as compared to BMI.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations